Cross-sectional associations of self-perceived stress and hair cortisol with metabolic outcomes and microvascular complications in type 2 diabetes - Buckert, Magdalena; Streibel, Carmen; Hartmann, Mechthild; Monzer, Nelly Lou; Kopf, Stefan; Szendrödi, Julia; Wild, Beate (Frontiers in Public Health, 2024)
INTRODUCTION: Increasing evidence supports chronic psychological stress as a risk factor for the development of type 2 diabetes. Much less is known, however, about the role of chronic stress in established diabetes. METHODS: The aim of the current study was to comprehensively assess chronic stress in a sample of 73 patients with type 2 diabetes and 48 non-diabetic control participants, and to investigate associations with indicators of glycemic control (HbA1c), insulin resistance (HOMA-IR), β-cell functioning (C-peptide), illness duration, and the presence of microvascular complications. Chronic stress was measured using questionnaires [the Perceived Stress Scale (PSS), the Screening Scale of the Trier Inventory of Chronic Stress (SSCS), the Perceived Health Questionnaire (PHQ) as well as the Questionnaire on Stress in Patients with Diabetes-Revised (QSD-R)]; hair cortisol was used as a biological indicator. RESULTS: We found that patients with type 2 diabetes had higher levels of hair cortisol in comparison to the control group (F(1,112) = 5.3; p = 0.023). Within the diabetic group, higher hair cortisol was associated with a longer duration of the illness (r = 0.25, p = 0.04). General perceived stress did not show significant associations with metabolic outcomes in type 2 diabetes patients. In contrast, higher diabetes-related distress, as measured with the QSD-R, was associated with lower glycemic control (r = 0.28, p = 0.02), higher insulin resistance (r = 0.26, p = 0.03) and a longer duration of the illness (r = 0.30, p = 0.01). DISCUSSION: Our results corroborate the importance of chronic psychological stress in type 2 diabetes. It appears, however, that once type 2 diabetes has developed, diabetes-specific distress gains in importance over general subjective stress. On a biological level, increased cortisol production could be linked to the course of the illness.